2013
DOI: 10.1093/ndt/gfs551
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of autosomal-dominant polycystic kidney disease: an in-depth clinical study for south-western Germany

Abstract: Prevalence of ADPKD is overestimated by 2- to 5-fold and close to the limit of RDs which may be of broad clinical, logistic and policy implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 28 publications
8
78
1
1
Order By: Relevance
“…This approach yielded an ADPKD diagnosed point prevalence on December 31, 2012, of 3.96 per 10,000. Other recently published European studies [17, 36, 37] have yielded similar prevalence estimates ranging from 3.3 to 4.6 per 10,000. Also consistent with these results, a recent European meta-analysis of 8 epidemiologic studies yielded an average prevalence of 2.7 per 10,000 (95% CI = 0.73–4.67) and a point prevalence of 3.63 per 10,000 in the province of Modena (Italy) [38].…”
Section: Discussionsupporting
confidence: 57%
“…This approach yielded an ADPKD diagnosed point prevalence on December 31, 2012, of 3.96 per 10,000. Other recently published European studies [17, 36, 37] have yielded similar prevalence estimates ranging from 3.3 to 4.6 per 10,000. Also consistent with these results, a recent European meta-analysis of 8 epidemiologic studies yielded an average prevalence of 2.7 per 10,000 (95% CI = 0.73–4.67) and a point prevalence of 3.63 per 10,000 in the province of Modena (Italy) [38].…”
Section: Discussionsupporting
confidence: 57%
“…Definite pathogenic mutations accounted for 69.9% of all identified mutations in the present study, which was comparable to the results from the previously reported 45.1–66.6% in Caucasian populations [8, 17, 31], but higher than the 27.7–52.2% reported in Asian populations [25, 32]. Among the definite pathogenic mutations, the large deletion mutation was a special one that was detected by MLPA analysis [15].…”
Section: Discussionsupporting
confidence: 92%
“…Among these 93 mutations, 59.1% were reported for the first time, and the remaining 40.9% were recurrent mutations. The recurrence rate was higher than in previous reports, ranging from 16.7% to 30% in Caucasian populations [8, 17, 31]. …”
Section: Discussioncontrasting
confidence: 66%
“…Population-based studies in a European population determined prevalence rates between 2.41 and 3.89/10,000 [12,13]. The European Renal Association and European Dialysis and Transplantation Association (ERA-EDTA) registry data provided prevalence data of 3.29/10,000 [14].…”
Section: Prevalencementioning
confidence: 99%